Growth and Value Effect on Jakarta Islamic Index: Analysis towards Performance of Sharia Equity Mutual Fund - Rusmita, Sylva Alif; Che Mohd Salleh, Marhanum; Sucia Sukmaningrum, Puji; Zulaikha, Siti (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
This study provides evidence that value and growth stocks are able to explain Net Asset Value of sharia mutual fund. Growth and value stocks in 2013-2017 are used to predict mutual fund profits. Thus, prior to any losses or lower Net Asset Value experienced by customers, investment managers and investors can estimate the profit or loss obtained. This study uses quantitative method with the latest secondary data from companies indexed in the Jakarta Islamic Index and sharia mutual fund data. The results of statistical tests show that growth and value shares equally affect the profit of sharia mutual funds. The growth stock has a larger R-Square than stock value. Meanwhile, the ratios that most affect Net Asset Value of sharia mutual fund are the Return on Equity and Book to Market Value. Penelitian ini membuktikan bahwa growth stock dan value stock mampu menjelaskan Net Asset Value dari mutual fund syariah. Growth stock dan value stock digunakan untuk memperdiksi keuntungan dari mutual fund. Sehingga, sebelum nasabah mengalami keuntungan atau kerugian atas Net Asset Value, manajer investasi dan investor dapat memprediksi kemungkinan keuntungan dan kerugian yang akan didapat. Artikel ini menggunakan metode kuantitatif dengan data sekunder yang diperoleh dari perusahanperusahaan yang terindeks oleh Jakarta Islamic Index dan data mutual fund syariah. Hasil penguajian data statistic menunjukkan bahwa baik growth stock maupun value stock mempengaruhi keuntung mutual fund syariah. Growth stock menunjukkan R-square lebih besar daripada stock value. Sementara itu, rasio yang paling berpengaruh terhadap Net Asset Value pada mutual fund syariah adalah Return on Equity dan Book to Market Value.